TINJAUAN SISTEMATIS TENTANG PENERAPAN PRINSIP ETIKA BISNIS PADA UMKM DI DIGITALISASI - Miftahqul Mauliddia Rokhmawati; Ach Fariz Surya Ramadhan; Adi Lukman Hakim; nuning nurna dewi (JEB17 : Jurnal Ekonomi dan Bisnis, 2026)
This research aims to understand the implementation of business ethics in MSMEs in the era of globalization. Micro, Small, and Medium Enterprises (MSMEs) play an important role in every country, including Indonesia, as they drive the economy and contribute to national development in this era of globalization. Based on the research results, many business actors still lack the implementation of business ethics such as honesty, fairness, and responsibility when selling products directly. This study identifies "How Business Ethics Are Implemented in the Digitalization Era." With increasingly advanced technology, business actors should be able to adapt, as technology is one of the methods that can support the development of a business. This can be realized in the form of promotion and sales through social media, as it will be more effective in increasing consumer attraction, and consumers have ample time to learn about products anytime and anywhere. Using a literature approach and secondary data analysis from national reports, this study found that the implementation of ethical principles such as transparency, honesty, and social responsibility positively impacts reputation and consumer loyalty, which ultimately enhances sales performance. The results of this study are expected to serve as a strategic reference for MSME actors in developing sustainable and ethical digital businesses.Keywords: Digitalization, Business Ethics, and SMEs